A systematic review of the research gaps in breast cancer in the gulf region - Sprakel, Julie Francis (2020)
To provide a high-quality, up-to-date, evidence-based resource with recommendations based on the GRADE approach and clinical algorithms to enable shared clinical decisions. Building on existing clinical practice guidelines the completed work provides a local voice via the strategic championship of a mostly local multidisciplinary team- which includes consumer advocates and patients. The overall effort changed the perception of a role of a Non-Governmental Organization (NGO) and highlighted a governmental/non-governmental partnership could fill the gaps and better support the community. This comprehensive and contemporary resource can be used across the continuum of breast cancer care for both healthcare providers and patients, to better navigate the clinical pathways and provide best practice recommendations for informed and shared decision making. The RAPADAPTE method provided rapid adaptation of guidelines and evidence resources and minimized unnecessary repetition, rather than developing the guideline de novo. RAPADAPTE builds on the well-established ADAPTE method and had been used to develop a similar breast cancer guideline for Costa Rica. This inclusive and innovative method involved a peer review process using tools such as AGREE II, Lenzer\'s Red Flags and the Institute of Medicine (IOM) criteria. This gave international credibility and up-to-date best practices to the first line professionals in health centres across the Kingdom, in relation to breast cancer diagnosis, screening and treatment. It was also designed to be readily accessible to the community in the format of patient pathways and algorithms. The establishment of the first interactive patient-centered, multidisciplinary approach to guideline development for breast cancer treatment, screening and diagnosis in Bahrain. This locally flavoured, evidenced based guideline not only used sharing of resources but was developed with little direct cost. Over 18 months the multidisciplinary team supported the development of 35 clinical scenarios relevant to the gamut of supporters along with treatment algorithms. Having an inclusive process and clear methodology meant that the multidisciplinary team championed the process and results, reducing some of the challenges. Whilst the guidelines provide an underpinning for future policy making and management of breast cancer in Bahrain the innovation is the identification of eight clinical scenarios in which shared decision making is recommended, thus empowering the end-user. This hands-on initiative at grass roots level addressed pertinent issues related across a multidisciplinary team, when supporting a patient through their treatment pathway is key. Singing all from the same \"hymn sheet\" is vital to better support and optimise and improve health outcomes. Reducing the confusion of what evidence based best practice is, whilst producing a locally flavoured document, showed that NGOs can be used as a resource in relation to Public Private Partnerships (PPP). This international peer reviewed guideline for Bahrain will ensure that there will be a joint clinician and patient focus, whilst recognising that the keys to success, adoption, implementation and sustainability lies with the government itself. Moving forward, the NGO is supporting the development of three of the eight shared decision-making aids the backing of international publishers of evidence- based clinical references (EBSCO).